Improving English speaking fluency in engineering students through problem-based learning (PBL) - Sadiyani, Ni Wayan; Mandang, Selvie Ratna Ivone; Somawati, Ni Putu (Yayasan Mitra Persada Nusantara, 2025)
English speaking fluency is a vital communication skill for engineering students, especially in the context of increasing global collaboration and the internationalization of higher education. However, many engineering students face persistent challenges in oral communication due to a lack of confidence, limited exposure to authentic speaking environments, and traditional language teaching methods that prioritize passive learning. This study explores the effectiveness of Problem-Based Learning (PBL) as an instructional approach to enhance English speaking fluency among engineering students. PBL is rooted in constructivist learning theory and emphasizes collaborative, learner-centered activities that simulate real-world problem-solving scenarios. Through a quasi-experimental research design, two groups of engineering students at a public university in Indonesia were observed over one academic semester. The experimental group engaged in PBL-driven English speaking sessions, while the control group received conventional speaking instruction. Pre- and post-intervention assessments, alongside qualitative data from classroom observations and student reflections, were analyzed to measure improvements in fluency, coherence, and language complexity. The results revealed that the PBL group demonstrated significantly higher gains in speaking fluency compared to the control group. Moreover, students reported increased motivation, reduced speaking anxiety, and greater engagement in communicative tasks. These findings suggest that integrating PBL into English for Specific Purposes (ESP) instruction can provide engineering students with meaningful opportunities to practice language in contextually rich and cognitively engaging environments. This research contributes to the growing body of literature on innovative pedagogy in language education and offers practical implications for curriculum designers, language instructors, and policymakers aiming to improve communicative competence in STEM fields. Future studies are recommended to examine long-term impacts and scalability across diverse educational settings.